ASSESSING THE IMPACT OF MAQASHID SHARIA ON THE SUBJECTIVE WELL-BEING OF INDONESIAN MUSLIMS: EVIDENCE FROM IFLS V - Neng Kamarni; Fatin Fadhilah Hasib; Debi Abdiska; Zulkifli N; Noraina Mazuin Sapuan (Universitas Airlangga, 2025)
Subjective well-being is shaped not only by economic conditions but also by a sense of happiness in this life and hope for the hereafter. This perspective suggests that a nation's progress should be viewed beyond economic growth alone. Maqashid Sharia, the five essential objectives in Islamic teachings, provides a framework that guides individuals toward a more holistic and meaningful well-being. This study aims to explore how Maqashid Sharia contributes to the subjective well-being of Muslim individuals in Indonesia. Using a quantitative approach, the analysis draws on data from the 2014 Indonesia Family Life Survey (IFLS) V, focusing on Muslim respondents aged over 18. Logistic regression is employed to assess the influence of five dimensions of Maqashid Sharia, protection of religion, life, intellect, lineage, and wealth on happiness. A few examples of control variables are sex, age, and place of residence. The findings demonstrate that each of the five facets of Maqashid Sharia has a significant and positive influence on the Muslims' subjective well-being in Indonesia. Those who are religious, healthy, well-educated, married, and employed tend to experience greater well-being. The well-being of women and younger generations is also higher, although residency does not appear to be a significant role. These results highlight the significance of measures that increase access to religious homes, healthcare, education, work, and marital readiness. putting the principles of maqashid sharia into practice in order to ensure the prosperity and well-being of Indonesian Muslims and to accomplish fair and significant agreements between economic reality and religious identity.